Protein Citrullination: A Proposed Mechanism for Pathology in Traumatic Brain Injury - Lazarus, Rachel C.; Buonora, John E.; Flora, Michael N.; Freedy, James G.; Holstein, Gay R.; Martinelli, Giorgio P.; Jacobowitz, David M.; Mueller, Gregory P. (Frontiers in Neurology, 2015)
Protein citrullination is a calcium-driven post-translational modification proposed to play a causative role in the neurodegenerative disorders of Alzheimer’s disease, multiple sclerosis (MS) and prion disease. Citrullination can result in the formation of antigenic epitopes that underlie pathogenic autoimmune responses. This phenomenon, which is best understood in rheumatoid arthritis, may play a role in the chronic dysfunction following traumatic brain injury (TBI). Despite substantial evidence of aberrations in calcium signaling following TBI, there is little understanding of how TBI alters citrullination in the brain. The present investigation addressed this gap by examining the effects of TBI on the distribution of protein citrullination and on the specific cell types involved. Immunofluorescence revealed that controlled cortical impact in rats profoundly up-regulated protein citrullination in the cerebral cortex, external capsule, and hippocampus. This response was exclusively seen in astrocytes; no such effects were observed on the status of protein citrullination in neurons, oligodendrocytes or microglia. Further, proteomic analyses demonstrated that the effects of TBI on citrullination were confined to a relatively small subset of neural proteins. Proteins most notably affected were those also reported to be citrullinated in other disorders including prion disease and MS. In vivo findings were extended in an in vitro model of simulated TBI employing normal human astrocytes. Pharmacologically-induced calcium excitotoxicity was shown to activate the citrullination and breakdown of glial fibrillary acidic protein, producing a novel candidate TBI biomarker and potential target for autoimmune recognition. In summary, these findings demonstrate that the effects of TBI on protein citrullination are selective with respect to brain region, cell type and proteins modified, and may contribute to a role for autoimmune dysfunction in chronic pathology following TBI.